Relationship of spiritual intelligence components with students’ adjustment - Mansouri, Morteza; Khorshidzade, Mohsen; Asgari, Ali (Penerbit Universiti Kebangsaan Malaysia, 2016)
The purpose of the research paper was to investigate the relationship between spiritual intelligence components with components of students’ adjustment among student at the University of Birjand. This study was descriptive and correlational. The population of this study were students that enrolled in the 2011-2012 school year, of which 210 of them (male and female students) were randomly selected. For data collection two questionnaires were used, the student adjustment questionnaire (Farahbakhsh) and spiritual intelligence questionnaire (King); that which reliability of the based on Cronbach’s alpha was 0.94 and 0.88, respectively. The results showed that there was a positive and significant relationship between the components of spiritual intelligence (Understand and communicate with the source being and Spiritual life) and the components of students’ adjustment (Social Adjustment, Emotional adjustment, Educational adjustment, Purposefulness and self-discovery, Institutional attachment). Also, the component of understand and communicate with the source being, cannot predict the students’ adjustment.The results showed that the relationship between spiritual intelligence and adjustment was significant. The relationship between understand and communicate with the source being and social adjustment was positive and significant. Also, there was a positive and significant relationship between spiritual life and social adjustment.